Exercícios de (des)aprender na poética de Manoel de Barros : memória, infância e natureza - Silva, Marla dos Santos (2019)
This master’s thesis aims to provide a deeper study of the poet Manoel de Barros. To achieve this aim, three thematic axis were chosen: biographic aspects, the link between memory and childhood and the dialogue between men and nature. A mapping of the poet’s published books is proposed resulting in a selection of verses which are relevant to the study. The biography section is based on Philippe Lejeune's (2008), Alfredo Bosi's (1977), Jacques Lacan's (2009) and Gaston Bachelard's (2002) theorical contributions. The memory and childhood section is grounded on Giorgio Agamben's (2005), Gaston Bachelard's (1988), Beatriz Sarlo's (2007), Michel Pollak's (1992) and EcléaBosi's (1979) productions. The analysis of the dialogue between man and nature contemplate Russeau's (1989) and Maria Esther Maciel's (2008/ 2011) considerations. The observations on poetry and language, which are intertwined in the analysis as a whole, are based on Octavio Paz' (2012), Luiz Costa Lima's (1995), Johan Huizinga's (2007) and Merleau-Ponty's (2002) theorical works. Manoel de Barro's poems are an invitation to a sensitive approach of man and nature, they explore the origins of the world, conducting the reader to a naive state such as that of a child's point of view. Through a language innovation, which undermines grammar rules, the poet renews the reader's views on the universe of the words, making an unveiling of the beings and a gathering with the hidden beauty of each and everything possible.